Optimization of Aspergillus niger lipase production by solid state fermentation of agro-industrial waste - Dwini Normayulisa Putri; Andy Khootama; Meka Saima Perdani; Tania Surya Utami; Heri Hermansyah (Energy Reports, 2020)
Lipase is one of the most used industrial enzymes, which can be produced by Aspergillus niger. Large scale production of Aspergillus niger lipase is more profitable by using solid state fermentation method and utilizing agro-industrial waste as the substrate. Optimization of Aspergillus niger lipase production has been performed in this study. Optimization was performed on solid state fermentation of rice bran and Jathropa seed cake for 5 days with variations of inducer and extractant. Fermentation cake produced was extracted, filtered using muslin cloth, and centrifuged. The supernatant was spray-dried and assayed using olive oil hydrolysis titrimetry. Inducer optimization results showed that 1% of olive oil was the best inducer, yielding dry lipase extract with highest activity unit (176 U/ml enzyme). Extractant optimization results showed that 1% of NaCl - 0.5% of Tween 80 was the best extractant, yielding dry lipase extract with highest activity unit (282 U/ml enzyme).
Keywords: 330; Agro-industrial waste; Lipase; Solid-state fermentation